Zygomatic air cell defect: A panoramic radiographic study of a south Indian population - HS, Srikanth (Medknow Publications, 2010)
AIMS: To determine the prevalence, patterns of occurrence and variations of zygomatic air cell defects (ZACDs) using panoramic radiographs. METHODS AND MATERIALS: Dental panoramic radiographs of 600 outpatients were examined to evaluate the variations and characteristics of ZACDs. RESULTS: ZACDs were identified in 15 subjects out of 600, giving an overall prevalence of 2.5%. Seven ZACDs were seen in males and eight in females. Among the 15 ZACDs, nine were unilateral and six were bilateral. CONCLUSION: The overall prevalence of ZACD is relatively low in south Indian population and careful radiographic evaluation is needed to detect these entities.